Praca grupowa jako narzędzie zwiększające efektywność zarządzania organizacją na przykładzie Volkswagen Motor Polska Sp. z o.o. - Mędrek, Sławomir (Team Work as a Tool Increasing the Organization Management Effectiveness on the Example of Volkswagen Motor Polska, 2008)
Nowadays, in the world of globalization and modern management tools, when all world-wide corporations have a possibility do access the newest technology, making use of knowledge and creativity of the employees, is beginning to gain importance. It is thanks to these resources that companies can gain an advantage over the competitors. Involving employees from the lowest levels of an organization in the management process allows to make use of the whole resources of the organization. This model has been used in the management process in Volkswagen Motor Polska. Introduction of team work, making use of the rank-and-file initiatives, in order to facilitate the processes and implement the holistic system of innovation management, enable more efficient competition both on the forum of Volkswagen corporation and on the forum of motorization market. A very important issue is the possibility to make use of knowledge that already exists within the corporation and to create conditions that facilitate sharing knowledge, which means that tools or system, that will make these processes easier, are required. Volkswagen made an attempt to make use of these resources through creating a data base that contains all submitted innovations, and allowing all employees access to them. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 561-568